2016
DOI: 10.21037/jtd.2016.10.12
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s agammaglobulinemia in an adult male due to a novel mutation: a case report

Abstract: X-linked agammaglobulinemia (XLA) is caused by mutation in the gene coding for Bruton's tyrosine kinase (BTK), which impairs peripheral B cell maturation and hypogammaglobulinemia. In this report, we present a case of XLA in a 22-year-old adult male. Genetic testing revealed a novel mutation located at the conserved region (c.383T>C). The patient had a history of recurrent respiratory tract infection which eventually progressed to chronic type II respiratory failure. Several pathogenic bacteria were isolated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…In the present case, despite the elevated levels of serum IgG, other common pathogenic microorganisms were absent compared with two other studies [ 8 , 9 ], and only CMV was detected. Serum IgG trough levels >500 mg/dL are generally accepted as the required minimum threshold for patients with primary immunodeficiency [ 21 ].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In the present case, despite the elevated levels of serum IgG, other common pathogenic microorganisms were absent compared with two other studies [ 8 , 9 ], and only CMV was detected. Serum IgG trough levels >500 mg/dL are generally accepted as the required minimum threshold for patients with primary immunodeficiency [ 21 ].…”
Section: Discussioncontrasting
confidence: 69%
“…Herein, we described the case of a patient with XLA presenting symptoms of CMV pneumonia, which was confirmed by serology and RT-PCR analysis of BAL fluid and sputum. To date, only two studies have reported CMV as the pneumonia-causing pathogen in patients with XLA ( Table 1 ) [ 8 , 9 ]. In these case studies, the patients were treated with antibiotics and IVIG, demonstrating treatable outcomes with and without ganciclovir therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although selective IgA deficiency is a mild form of immunodeficiency, some patients develop a variety of significant clinical problems, such as CMC (70). Furthermore, Candida infections in individuals with Xlinked agammaglobulinemia (XLA), a mutation in the gene encoding for Bruton tyrosine kinase (BTK) which leads to impaired peripheral B cell maturation, have been described (71)(72)(73). Lymphoid cancers patients treated with ibrutinib, a BTK inhibitor, develop invasive fungal infections including candidemia (74).…”
Section: Discussionmentioning
confidence: 99%
“…While BTK deficiency can leave the body in a state of immunodeficiency (e.g., XLA), its upregulation may lead to autoimmune states, such as rheumatoid arthritis and systemic lupus erythematosus [19], as well as malignant states, notably B-cell malignancies [23], squamous cell carcinoma, and pancreatic cancer [24]. Hundreds of variants have been identified in the gene BTK from patients with XLA [25][26][27][28][29]18] which may explain phenotypic divergence in XLA [30]. Therefore, data are integrated to investigate genotype-phenotype interactions [31].…”
Section: X-linked Agammaglobulinemia (Bruton's Disease or Btk Deficiementioning
confidence: 99%